Pengaruh Financial Threat terhadap Willingness to Change Financial Behavior, dan Psychological Distress - Rasyidi Faiz Akbar; Fiona Niska Dinda Nadia; Eka Bambang Gusminto; Susilowati Susilowati (Nomicpedia: Journal of Economics and Business Innovation, 2023)
Financial threats are defined as fearful uncertainties regarding current and future financial situations. The purpose of this research is to test the theoretical model of the relationship between financial threats to psychological distress and individual willingness to change their financial behavior. Consistent across samples, SEM-PLS modeling revealed that the data fit the model and supported all four hypotheses. Positive financial threat with willingness to change, job search, and psychological stress. The practical implications of the findings are discussed.